Teachers’ perception of the effectiveness of computer technology in an ELT classroom/ Lis Chin Chong - Chin Chong, Lis (2008)
The aims ofthis study are to find out the frequency or extent of computer technology use for the teaching and learning of the English Language in the classroom and teachers’ perception of its effectiveness in ELT classroom. The Malaysian Government has invested Millions of Ringgit into this mega project with the aim of boosting the computer usage in schools because of the realization of its importance towards enhancing the effectiveness of ELT in schools alongside the teaching of Mathematics and science in English. It is hoped that the findings and recommendations presented in this research would be able to help the teachers to realise the importance of computer technology and their (teachers) vital role in making it successful. This can only be achieved when the teachers who are the key players, have the right attitude and perception regarding the effectiveness of the computer technology in an ELT classroom.